Marketing Strategy Formulation for the Introduction of Eukula Strato German Wood Finishes in Local Market of Emerging Indian Economy - Suraj Kushe Shekhar; Mehaboob P K (Hyperion Economic Journal, 2013)
Wood finishing relates to the process of embellishing or protecting the surface of the wood. The paper aimed at formulating a marketing strategy for introducing water borne German based Wood Finishes named Eukula Strato into local market of northern Kerala, India. Multiple cross sectional descriptive research with judgmental sampling technique elicited responses from Finishers, Furniture manufacturers and Interior designers. Findings revealed that Eukula Strato had a distinct advantage when compared to any other Wood Finish that was available in the local market. Findings and suggestions were reported as per 4P’s of marketing mix. Percentage analysis, Chi square analysis etc were used to interpret the results